Impact of Youth Health Ambassador Programme on health awareness in youths in Singapore - Shermane Y. W. Lim; Ryan J. Loh; Yao Hao Teo; Elliot Y. Chong; Zhong Chen Tan; Sherry D. X. Du; Abigail K. Lee; Yi Ping Ren; Joshua Chia; Desmond B. Teo; Fong Seng Lim (Wolters Kluwer Medknow Publications, 2024)
BACKGROUND: The Youth Health Ambassador Programme (YHAP) is a health educational program aimed at empowering youths to become health ambassadors in the community through raising their health awareness and training them in primary health prevention. This study evaluates the effectiveness of YHAP in improving the knowledge, attitudes, and practices (KAP) of participants in physical and mental health. MATERIALS AND METHODS: This study followed a single-group quasi-experimental design, with a pre- and postworkshop KAP survey. Participants were junior college (JC) and polytechnic students in Singapore enrolled in YHAP. In total, 131 responses were analyzed for changes in KAP for physical and mental health before and after the program. This article also studied the participants' barriers to educating others, including environment factors, intrinsic factors, and receptiveness of the target audience. RESULTS: Mean scores of all six KAP domains increased from the preworkshop survey to the postworkshop survey, with significant improvements (P < 0.05) in all domains except mental health knowledge. Individually, 16 out of 29 questions in the KAP sections had a significant increment in mean score after the program (P < 0.05). Mean scores for intrinsic barriers also decreased significantly (P < 0.001) postintervention, indicating that participants were less likely to agree that intrinsic factors were a barrier to educating people around them about health postintervention. CONCLUSION: YHAP is effective in improving the KAP of physical health and the attitudes and practices of mental health JC and polytechnic students and may reduce the effect of intrinsic barriers that participants face when teaching others.